Patterns and impacts of patient migration for primary knee arthroplasty in China: A national retrospective study - Fanqiang Meng; Xinjia Deng; Junzhi Sheng; Haoran Feng; Liusong Shen; Hu Chen; Dongxing Xie; Huizhong Long (PLoS ONE, 2025)
Objective The phenomenon of interregional patient migration for primary knee arthroplasty (KA) appeared due to unbalanced distribution of medical resources. However, there is a paucity of literature about migration among patients receiving primary KA and the possible influence of migration on postoperative outcomes and financial burden. This study was aimed to investigate the characteristics of patient migration for KA in China and evaluate the related impacts. Methods Primary KAs performed between 2013 and 2018 were retrieved from the Hospital Quality Monitoring System in China. Cross-province (i.e., 31 provinces of mainland China) attendance for KA was assessed. Propensity score-matched analysis was conducted to evaluate the effect of migration on postoperative outcomes and financial burden. Results A total of 168,693 primary KA patients were included during the study period. The migration rate decreased from 17.6% in 2013 to 7.6% in 2018 (P < 0.001). Migration occurred more frequently in patients with fewer comorbidities. Migrating patients tended to choose provincial hospitals and hospitals with high procedure volumes. Beijing and Shanghai were the most preferred destinations. After matching, there were no significant differences in in-hospital mortality, pulmonary embolism, deep vein thrombosis, wound infection, or 30-day readmission between two groups. The migration group had much higher total hospital charges. Conclusion A noticeable number of patients required cross-province migration to get access to KA. Migration didn’t make a big difference but caused a greater financial burden. It is imperative to take initiatives to reduce disparities in resource allocation instead of relying on cross-district access.